Peran Pendidikan Karakter Berbasis Aswaja dalam Mencegah Radikalisme - Waladan As'ada; Ali As’ad; Yayan Adi Saputro (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
The problems that often haunt radicalism among the younger generation are a serious challenge to the integrity of the Republic of Indonesia. With the form of actions to separate themselves from the nation, create their own group alliances, and others that cause the integrity of the state and religion to be at stake. Character education based on Ahlussunnah wal Jama'ah (Aswaja) offers a peaceful prevention approach through the values of moderation in religion, tolerance, and nationalism. This study aims to analyze and understand in depth the Role of Aswaja-Based Character Education in Preventing Radicalism. The method used is qualitative descriptive with case studies in educational institutions that implement the Aswaja curriculum. The steps taken in using literature studies, in-depth interviews and documentation. The data analysis method in this study uses steps, namely data reduction, data display (presentation) and conclusions. While checking the validity of the data using triangulation. strategies to prevent students' understanding of radicalism, The results of the study show that the integration of Aswaja values in intracurricular and extracurricular activities is effective in forming moderate and tolerant student characters. The conclusion of this study confirms the importance of Aswaja-based character education as a deradicalization strategy in the educational environment. First, by increasing the religious rituals of Ahlusunah waljamaah. and forming positive habits in teaching Aswaja values. While the implication is to develop Aswaja learning and instill the noble values of Aswaja to students. So that they are able to fortify themselves from the influence or invitation of radical groups.